Technology Standardization for Innovation: How Google Leverages an Open Digital Platform - Yoshiaki Fukami; Takumi Shimizu (Information, 2021)
The aim of this study is to investigate firms’ strategies for developing and diffusing technology standards while maintaining a consensus with competitors in their industry. We conducted a case study of information technology (IT) standardization and analysed how Google drives the development and diffusion of HTML5 standards. Accordingly, this study sheds light on two strategic initiatives and two relational practices of standard development and diffusion. Adopting the technologies developed by other firms and forming alliances with other browser vendors are key to influencing the standardization process. Additionally, by building partnerships with developer communities, Google has accelerated the development and diffusion of the HTML5 standards. The mechanisms behind Google’s standardization strategies are also discussed.